Lonicerae Japonicae Flos with the homology of medicine and food: a review of active ingredients, anticancer mechanisms, pharmacokinetics, quality control, toxicity and applications - Ma, Ping; Yuan, Ling; Jia, Shumin; Zhou, Ziying; Xu, Duojie; Huang, Shicong; Meng, Fandi; Zhang, Zhe; Nan, Yi (Frontiers in Oncology, 2024)
Lonicerae Japonicae Flos (LJF, called Jinyinhua in China), comes from the dried flower buds or flowers to be opened of Lonicera japonica Thunb. in the Lonicera family. It has a long history of medicinal use and has a wide range of application prospects. As modern research advances, an increasing number of scientific experiments have demonstrated the anticancer potential of LJF. However, there is a notable absence of systematic reports detailing the anti-tumor effects of LJF. This review integrates the principles of Traditional Chinese Medicine (TCM) with contemporary pharmacological techniques, drawing upon literature from authoritative databases such as PubMed, CNKI, and WanFang to conduct a comprehensive study of LJF. Notably, a total of 507 compounds have been isolated and characterized from the plant to date, which include volatile oils, organic acids, flavonoids, iridoids, triterpenes and triterpenoid saponins. Pharmacological studies have demonstrated that LJF extract, along with components such as chlorogenic acid, luteolin, rutin, luteoloside, hyperoside and isochlorogenic acid, exhibits potential anticancer activities. Consequently, we have conducted a comprehensive review and summary of the mechanisms of action and clinical applications of these components. Furthermore, we have detailed the pharmacokinetics, quality control, and toxicity of LJF, while also discussing its prospective applications in the fields of biomedicine and preventive healthcare. It is hoped that these studies will provide valuable reference for the clinical research, development, and application of LJF.